Factors influencing on lactation - M. V. Gmoshinskaya (Вопросы современной педиатрии, 2013)
All factors influencing on lactation can be divided into 4 groups: organizational, medical, psychological and social. Among the last ones family support, solving of social problems in the family, formation of comfort conditions for breast-feeding, psychological state of the mother and her ability to relax during breast-feeding have the main significance. Formed maternity instinct and developed lactation dominant during pregnancy, understanding of the significance of breast-feeding among the family and society, making of the comfort conditions for breast-feeding in medical institutions of obstetrics and childhood during the second stage of care, in domestic conditions — all these contribute to the maintenance of breast-feeding.